High virulence of a naturally occurring entomopathogenic fungal isolate, Metarhizium (Nomuraea) rileyi, against Spodoptera frugiperda - Yan‐li, Zhang; Hui, Dong; Li‐sheng, Zhang; Zu‐min, Gu; Jin‐cheng, Zhou (Journal of applied entomology (1986), 2022)
The fall armyworm (FAW), Spodoptera frugiperda, is a new and dangerous invasive pest in many countries. Entomopathogenic fungi (EPF) have been considered as potential biological control agents against the FAW. In this study, eight natural fungal strains were isolated from diseased larvae of FAW, and identified as Cladosporium cladosporioides (EFNL‐1), Metarhizium rileyi (EFNL‐2 and EFNL‐8), Fusarium proliferatum (EFNL‐3 and EFNL‐6), F. equiseti (EFNL‐4 and EFNL‐5) and F. tricinctum (EFNL‐7), using the morphological and molecular tools or methods. The instantaneous death risk and mortality of 3rd‐instar larvae inoculated with EFNL‐8 (1 × 108 conidia/ml) were significantly higher than for any other fungal isolates and for the control group. Thereafter, we tested the pathogenicity of EFNL‐8 (1 × 107 conidia/ml) against 1st‐ to 4th‐larvae, pupae, and eggs of FAW. The instantaneous death risk and mortality of 1st‐instar (Median lethal time = 9.02 days; Corrected motality = 88.68%), 2nd‐instar (12.00 days; 62.50%) and 3rd‐instar larvae (13.79 days; 56.67%) inoculated with EFNL‐8 were significantly higher than that of larvae in the control groups. When the eggs of FAW were inoculated with EFNL‐8 (1 × 107 conidia/ml), EFNL‐8 caused eggs (56.62%), and newly hatched neonates after 3 days (68.75%) and 6 days (80.60%) mortality, compared with the control groups. However, the mortality of the EFNL‐8 isolate to 4th‐instar larvae (5.00%) and pupae (14.81%) was low and did not differ from the control groups. This study identified M. rileyi EFNL‐8 as a pathogenic isolate against eggs and 1st‐ to 3rd‐instar larvae of FAW. However, further studies including field validation of this EPF biopesticide candidate should be undertaken in newly invaded areas by the pest.